Upaya Pengentasan Kemiskinan Melalui Program Keluarga Harapan - Azizah, Amalia Nur (Universitas Musamus,Merauke,Papua, 2023)
Poverty is a multidimensional problem that until now has become a world discussion. Poverty is also included in the main points of sustainable development (SDG's), therefore poverty reduction is a shared responsibility and comprehensive handling is needed, involving many parties and many sectors. One of the efforts made by the Indonesian government in poverty alleviation is the family hope program. This program has been launched since 2007 and is still running. The purpose of this study is to find out how the implementation of the Family Hope Program, inhibiting factors and what efforts are made to overcome these inhibiting factors. Method: This study used descriptive qualitative method. The data used in this study are secondary data obtained from previous research sources, which come from aticles, news, and social ministry sites. The results of this study show that PKH has provided benefits for its recipients, but still has shortcomings, namely the recipients of PKH assistance are limited where there are still many people who meet the criteria as PKH participants but are not registered as participants because they have met the quota that has been prepared.